Metabolomics paves the way for improved drug target identification - Belinda B Garana; Nicholas A Graham (Molecular Systems Biology, 2022)
Abstract Correctly identifying candidate drugs for protein targets is crucial for drug discovery. Despite the importance of this problem for the pharmaceutical industry, chemical screening remains a challenging task, and drug–target misidentification may contribute to failures in drug development. In their recent study, Sauer and colleagues (Holbrook‐Smith et al, 2022) demonstrate proof‐of‐concept for a new way to identify drug–target interactions using high‐throughput metabolomics, potentially paving the way towards a universal method for predicting drug–target relationships.